Atrioventricular Area Difference Assessed by Exercise Cardiovascular Magnetic Resonance Shows Impaired Diastolic Filling in Heart Failure Patients - Edlund, Jonathan ; 0000-0003-4957-7276; Östenson, Björn ; 0000-0003-2016-9631; Åkesson, Julius; Heiberg, Einar ; 0000-0003-2848-3326; Arheden, Håkan; Steding-Ehrenborg, Katarina (Journal of Applied Physiology, 2026)
Heart failure (HF) is a complex clinical syndrome characterized by exercise intolerance. However, most diagnostic assessments are performed at rest, when many patients are asymptomatic. To better understand the underlying pathophysiology, examination during exercise is needed. Hydraulic force, a newly identified mechanism of diastolic filling, is proportional to the difference in short-axis areas between the left ventricle and atrium, known as the atrioventricular area difference (AVAD). While hydraulic force has been shown to augment diastolic filling during exercise in healthy individuals, its role in HF during exercise remains unexplored. This study aimed to investigate whether hydraulic forces impair or augment diastolic filling in HF patients during exercise, using AVAD measurements from exercise cardiovascular magnetic resonance (CMR) imaging. We examined 13 healthy volunteers and 22 HF patients at rest and during exercise using a CMR-compatible ergometer. AVAD was measured at end-systole (ES) and end-diastole (ED). In HF patients, AVAD at ED decreased during exercise (from 17±5 cm2 to 15±6 cm2, p = 0.006), whereas it increased in healthy volunteers (from 16±3 cm2 to 17±3 cm2, p = 0.014). AVAD at ES decreased in both HF (from -2±5 cm2 to -8±5 cm2, p < 0.001) and healthy volunteers (from -3±2 cm2 to -5±3 cm2, p = 0.011). In conclusion, the results suggest impaired diastolic function during exercise in HF through reduced hydraulic force compared to rest. These findings provide new mechanistic insights and may partly explain the hallmark symptom of exercise intolerance in heart failure.